A novel composite perovskite-based material for chemical-looping steam methane reforming to hydrogen and syngas. (1st September 2018) - Ding, Haoran; Xu, Yongqing; Luo, Cong; Wang, Qiyao; Shen, Cheng; Xu, Jiaxin; Zhang, Liqi
Highlights: CeO2 supported BaCoO3−δ (BaCoO3−δ /CeO2 ) perovskites-type oxides were synthesized by sol-gel method. The BaCoO3−δ /CeO2 achieved high productions of syngas and hydrogen comparing with pure CeO2 and BaCoO3−δ . The BaCoO3−δ /CeO2 enhanced partial oxidizing of methane with high selectivity. CeO2 could supply oxygen to BaCoO3−δ for partial oxidation of methane. The BaCoO3−δ /CeO2 had an excellent performance in cyclic CL-SMR experiments. Abstract: Chemical looping steam methane reforming (CL-SMR) is a novel process that uses oxygen carriers to produce synthesis gas and pure hydrogen with low energy consumption. To enhance reactivity and selectivity of oxygen carriers, CeO2 -supported BaCoO3−δ perovskite-type oxides (BaCoO3−δ /CeO2 ) are synthesized by sol-gel method, and gas production in CL-SMR is investigated in a fixed-bed reactor. When compared with pure BaCoO3−δ and CeO2, BaCoO3−δ /CeO2 features higher productions of syngas and hydrogen, and the H2 /CO ratio is closer to the ideal value of 2. Gas production rates and H2 /CO ratios show that optimal reaction temperature is approximately 860 °C, and the optimal BaCoO3−δ to CeO2 mass ratio is 1/4. The maximum syngas production in fuel reactor measures 265.11 ml/g (oxygen carrier), whereas hydrogen production in reforming reactor is 82.53 ml/g (oxygen carrier). Perovskite samples were characterized using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and field emission scanning electron microscopy (FESEM) measurements. XRD results suggest that a part of CeO2 can supply oxygen to BaCoO3−δ for partial oxidation of methane and can be converted to CeO1.675 . Co obtained from methane reaction can split water to generate hydrogen. Crystal structure can be recovered during cyclic experiments, and XPS results indicate that lattice oxygen is the primary driver for syngas production. FESEM show that CeO2 particles are coated with BaCoO3−δ perovskite and the morphology of BaCoO3−δ /CeO2 samples does not change during reactions. CeO2 core can supply oxygen to the BaCoO3−δ perovskite, and the synergistic effect of CeO2 and BaCoO3−δ can improve gas production and composition.